Pola Asuh Single Parent dalam Membentuk Nilai Agama dan Moral Anak Usia 4-5 Tahun di Desa Simpang Agung - Yani, Dia Fitri; Rukiyah, Rukiyah (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines single-parenting styles in shaping religious and moral values in children aged 4-5 years in Simpang Agung Village. Understanding these patterns helps determine their impact on children’s moral and religious development.Method – A qualitative case study approach was used, involving six single parent as primary subjects and their children as secondary informants. Data was collected through interviews, observations, and documentation, then analyzed through four stages: collection, reduction, presentation, and conclusion drawing. Techniques and time triangulation ensure data validity and consistency in parenting. Findings – The study identified three parenting styles: authoritarian (33%), permissive (17%), and democratic (50%). Authoritarian parenting enforces strict rules, leading to obedience based on fear rather than understanding. Permissive parenting grants excessive freedom, resulting in low discipline and lack of moral awareness. Democratic parenting balances discipline and independence, engaging children in discussions and modeling moral behavior. Among the styles, democratic parenting proved most effective in fostering moral and religious values. Children raised with this approach show stronger moral reasoning and a deeper understanding of religious teachings. Research Implications – This study enriches theories on parenting and children's religious and moral development. Practically, it helps single parents adopt effective parenting styles. Policymakers can use these findings for parenting programs. However, limitations include a small sample, short-term focus, and limited cultural analysis. Future research should involve more subjects, assess long-term effects, and explore cultural influences for deeper insights.